The Value of Art and Culture in Everyday Life: Towards an Expressive Cultural Democracy. Issue 5 (19th October 2016) - Juncker, Beth; Balling, Gitte
ABSTRACT: Ever since the earliest forms of mass media, the dichotomy of mass culture/high culture has been a topic of debate. The concept of cultural democracy has developed as a way to acknowledge a variety of cultural activities. Despite attempts to develop a broader understanding of culture, cultural policy still seems to reproduce the dichotomies, and to value one over the other. In this article, we would argue for an expanded understanding of cultural democracy, which may serve as a starting point for a turn of perspective of arts advocacy and cultural policy—the perspective we call an expressive cultural democracy.